Novel quinazoline and acetamide derivatives as safe anti-ulcerogenic agent and anti-ulcerative colitis activity - Alasmary, Fatmah A.S.; Awaad, Amani Shafeek; Alafeefy, Ahmed Mahmoud; El-Meligy, Reham M.; Alqasoumi, Saleh Ibrahim (Elsevier, 2018)
Two novel quinazoline derivatives named as; 3-[(4-hydroxy-3-methoxy-benzylidene)-amino]-2-p-tolyl3H-quinazolin-4-one (5) and 2-p-Tolyl-3-[3,4,5-trimethoxy-benzylidene-amino]-3H-quinazolin-4-one (6) in addition to one acetamide derivative named as 2-(2-Hydroxycarbonylphenylamino)-N-(4- aminosulphonylphenyl) 11 were synthesized, and evaluated for their anti-ulcerogenic & AntiUlcerative colitis activities. All of the three compounds showed curative activity against acetic acid induced ulcer model at a dose of 50 mg/kg, they produced 65%, 85% & 57.74% curative ratio for compounds 5, 6 & 11 respectively. The effect of the tested compounds 5, 6 & 11 at dose 50 mg/kg were significantly (P < 0.01) more effective than dexamesathone (0.1 mg/kg) in reducing all parameters. Compounds showed curative activity of for peptic ulcer (induced by absolute alcohol (at a dose of 50 mg/kg, it produced Curative of control ulcer 56.00%, 61.70% & 87.1% for compounds 5, 6 & 11 respectively at dose 50 mg/kg, while the standard drug (Omeprazole 20 mg/kg) produced 33.3%. In both tests, the activity of our target compounds were higher than the standard drugs used for treatment of peptic ulcer and ulcerative colitis. No side effects were reported on liver and kidney functions upon prolonged oral administration of this compounds.